Inter-laboratory variability of A549 epithelial cells grown under submerged and air-liquid interface conditions. (September 2021) - Barosova, Hana; Meldrum, Kirsty; Karakocak, Bedia Begum; Balog, Sandor; Doak, Shareen H.; Petri-Fink, Alke; Clift, Martin J.D.; Rothen-Rutishauser, Barbara
Abstract: In vitro cell models offer a unique opportunity for conducting toxicology research, and the human lung adenocarcinoma cell line A549 is commonly used for toxicology testing strategies. It is essential to determine whether the response of these cells grown in different laboratories is consistent. In this study, A549 cells were grown under both submerged and air-liquid interface (ALI) conditions following an identical cell seeding protocol in two independent laboratories. The cells were switched to the ALI after four days of submerged growth, and their behaviour was compared to submerged conditions. The membrane integrity, cell viability, morphology, and (pro-)inflammatory response upon positive control stimuli were assessed at days 3, 5, and 7 under submerged conditions and at days 5, 7, and 10 at the ALI. Due to the high variability of the results between the two laboratories, the experiment was subsequently repeated using identical reagents at one specific time point and condition (day 5 at the ALI). Despite some variability, the results were more comparable, proving that the original protocol necessitated improvements. In conclusion, the use of detailed protocols and consumables from the same providers, special training of personnel for cell handling, and endpoint analysis are critical to obtain reproducible results across independent laboratories. Highlights: An exemplar study highlighting the advantages and pitfalls of inter-laboratory study. Detailed SOP development enabled comparable results for A549 cell responses. Consistency in training and approach are critical to any inter-laboratory study